2009
DOI: 10.1080/00016340902926734
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality and severe morbidity from sepsis in the Netherlands

Abstract: With a case fatality rate of 7.7%, sepsis is a life threatening condition for women during pregnancy, childbirth, and puerperium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 20 publications
13
118
2
2
Order By: Relevance
“…These include studies of sepsis in obstetric populations,6, 9, 10, 11, 30 and other morbidities in obstetric populations 12, 13, 14, 27, 31, 32. Interestingly, all those studies found an effect of at least one socio‐demographic factor, most commonly age, body mass index (BMI) or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…These include studies of sepsis in obstetric populations,6, 9, 10, 11, 30 and other morbidities in obstetric populations 12, 13, 14, 27, 31, 32. Interestingly, all those studies found an effect of at least one socio‐demographic factor, most commonly age, body mass index (BMI) or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, the maternal CFR from severe sepsis can be higher as in the Netherlands where it was 7.7% and the maternal mortality rate from sepsis was Group A Streptococcal Infections 867 0.7 per 100,000 live births. 5 Today, GAS produces a substantial amount, from 40% to over 50%, of maternal mortality related to sepsis in developed countries. 5,18 Over 80% of the neonates of women with invasive GAS infection remained well, and whereas no neonatal deaths occurred, septic abortion, abortion, and stillbirth occurred among women with invasive GAS.…”
Section: Epidemiologymentioning
confidence: 99%
“…5 Today, GAS produces a substantial amount, from 40% to over 50%, of maternal mortality related to sepsis in developed countries. 5,18 Over 80% of the neonates of women with invasive GAS infection remained well, and whereas no neonatal deaths occurred, septic abortion, abortion, and stillbirth occurred among women with invasive GAS. 18…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Then bacteria are able to reproduce and reach numbers in excess of 10 5 per milliliter of amniotic fluid 27 . Risk factors for the development of maternal sepsis include home birth in unhygienic conditions, low socioeconomic status, poor nutrition, primiparity, anaemia, prolonged rupture of membranes, prolonged labour, multiple vaginal examinations in labour (more than five), caesarean section, multiple pregnancy, artificial reproductive techniques, overweight and obstetrical manoeuvres 14,28 .…”
Section: Risk Factors and Routes Of Infection In Pregnancymentioning
confidence: 99%